A phenomenographical study of the qualitative variation of adventure / wilderness programme experiences among adolscent high school participants in the Western Cape - Zygmont, Conrad Stanislaw (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.